(untitled) (Research, Society and Development, 2021)
Objective: To understand and review the importance of including men in the prenatal care of their partners in Primary Health Care services. Methods: This is an integrative literature review, carried out between September 2020 and March 2021, through search for articles in the following databases: Scientific Eletronic Library Online (Scielo), Virtual Health Library (VHL), Google Scholar, National Center for Biotechnology Information (PubMed), Latin American and Caribbean Literature in Health Sciences ( Lilacs), Nursing Journals. The inclusion criteria were articles in Portuguese, English and Spanish, covering the years 2007 to 2021. The exclusion criteria are studies based on monetary reward, and materials that have no relevance to the proposed theme. Results: It is evident that it is not only the woman’s role to perform exams in the prenatal period, so the policy called “male prenatal care” aims to encourage the father to attend the Health Service in a preventive manner, in addition to stimulating the bond affective relationship between father, wife and child. Final considerations: This study demonstrated that health professionals must be able to expand the male public’s access to Primary Health Care services, offering welcoming, integration into existing programs, ease of care, and development of strategies specific to this group population, as well as the inclusion of men in the prenatal care of their partners, enabling the creation of a bond between father and son since pregnancy, in addition to the opportunity to carry out tests and check the vaccination situation.